2015
DOI: 10.1016/j.ygyno.2015.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Formation of stable small cell number three-dimensional ovarian cancer spheroids using hanging drop arrays for preclinical drug sensitivity assays

Abstract: Background Ovarian cancer grows and metastasizes from multicellular spheroidal aggregates within the ascites fluid. Multicellular tumor spheroids are therefore physiologically significant3Din vitro models for ovarian cancer research. Conventional hanging drop cultures require high starting cell numbers, and are tedious for long-term maintenance. In this study, we generate stable, uniform multicellular spheroids using very small number of ovarian cancer cells in a novel 384 well hanging drop array platform. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
102
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 40 publications
6
102
0
2
Order By: Relevance
“…We have previously demonstrated that by utilizing hanging drop plates, which provide a 3D environment to culture few to single cells at a time, we can recapitulate the key features of the innate tumor microenvironment. The hanging drop method has been found to more closely mimic the outcomes of drug success in vivo, providing a more accurate representation of effectiveness and patient response [911]. …”
Section: Introductionmentioning
confidence: 99%
“…We have previously demonstrated that by utilizing hanging drop plates, which provide a 3D environment to culture few to single cells at a time, we can recapitulate the key features of the innate tumor microenvironment. The hanging drop method has been found to more closely mimic the outcomes of drug success in vivo, providing a more accurate representation of effectiveness and patient response [911]. …”
Section: Introductionmentioning
confidence: 99%
“…With this combinatory approach, it will be possible to gain a more complete picture of the cancer microenvironment and ascertain potential avenues of treatment. Additionally, non-cell factors such as chemotaxis, 130 3D culture 94,[131][132][133][134][135][136] , and hypoxia 137 should be considered for future investigations, in conjunction with mechanical cues to create a microenvironment that can more fully recapitulate in vivo conditions. The study of ovarian cancer mechanotransduction promises to improve patient treatment through future investigations that utilize designs pertinent to the specific microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Several methods are used to generate 3-D multicellular tumor spheroids including: (i) Bioreactors(BRs) in which cells or spheroids aggregate in the chamber; [38][39][40] (ii) nonadherent plates that prevent attachment; 41,42 (iii) hanging-drop (HD) plates where cells are grown in a suspended droplet to form one single spheroid; [43][44][45][46] (iv) multicellular layers; [47][48][49] and (v) organoid culture 50,51 among others. In this paper, BDI was used to assess the different cellular responses to paclitaxel of cancer spheroids obtained by using the three most common approaches: BR, HD, and nonadherent plate growth.…”
Section: Methodsmentioning
confidence: 99%